The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/suco.201800113
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study and associated mechanism analysis of horizontal bolted connections involved in a precast concrete shear wall system

Abstract: This paper is concerned about the lateral load response and associated working mechanism of a precast reinforced concrete shear wall involving horizontal connections. An assembling method is proposed using dry connection through a horizontal steel connector (H-connector) and high strength bolts. To investigate the effectiveness of such an assembling method, two identical wall-connector assembly specimens have been constructed and tested under monotonic loading and cyclic loading, respectively, while subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Several connection systems have been experimentally and analytically investigated by the researchers worldwide. These include steel H connector, friction based devices, threaded anchors, vertical seam, joint connecting beam, dowel bars, O‐connectors, loop bar connection, steel angle and splice sleeve connection, multiple shear keys, vertical interlocking joint (PCI MNL 123–88). However, most of these connections require more investigations and are seldom used in construction industry.…”
Section: Joint Connectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several connection systems have been experimentally and analytically investigated by the researchers worldwide. These include steel H connector, friction based devices, threaded anchors, vertical seam, joint connecting beam, dowel bars, O‐connectors, loop bar connection, steel angle and splice sleeve connection, multiple shear keys, vertical interlocking joint (PCI MNL 123–88). However, most of these connections require more investigations and are seldom used in construction industry.…”
Section: Joint Connectionsmentioning
confidence: 99%
“…The system demonstrated low energy dissipation, strength deterioration, and stiffness degradation . Precast walls connected with H connector and steel bolts having high strength performed satisfactorily with favorable deformation characteristics under monotonic and cyclic loading . Bora et al developed a slotted‐bolted mechanical connection for joining precast hollow core wall with the floor slab.…”
Section: Joint Connectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of horizontally bolted connections on a precast concrete shear wall system has been investigated, and it has been confirmed that the ductility capacity was sufficient at the joints of the system through monotonic and cyclic material loading. Based on the experimental results, a new design approach was proposed …”
Section: Introductionmentioning
confidence: 99%
“…Based on the experimental results, a new design approach was proposed. 35 The structural performance tests on shear studs can be classified into pull-out and push-out tests, depending on the direction of the load applied to the concrete specimen. A compressive load is applied to the support of the concrete structure during a push-out test, whereas a tensile load is applied during a pull-out test.…”
Section: Introductionmentioning
confidence: 99%